A fully coupled multiphase model for infrared‐convective drying of sweet potato. (12th August 2020) - Onwude, Daniel I; Hashim, Norhashila; Chen, Guangnan; Putranto, Aditya; Udoenoh, Nsikak R
Abstract: BACKGROUND: Combined infrared (CIR) and convective drying is a promising technology in dehydrating heat‐sensitive foods, such as fruits and vegetables. This novel thermal drying method, which involves the application of infrared energy and hot air during a drying process, can drastically enhance energy efficiency and improve overall product quality at the end of the process. Understanding the dynamics of what goes on inside the product during drying is important for further development, optimization, and upscaling of the drying method. In this study, a multiphase porous media model considering liquid water, gases, and solid matrix was developed for the CIR and hot‐air drying (HAD) of sweet potato slices in order to capture the relevant physics and obtain an in‐depth insight on the drying process. The model was simulated using Matlab with user‐friendly graphical user interface for easy coupling and faster computational time. RESULTS: The gas pressure for CIR‐HAD was higher centrally and decreased gradually towards the surface of the product. This implies that drying force is stronger at the product core than at the product surface. A phase change from liquid water to vapour occurs almost immediately after the start of the drying process for CIR‐HAD. The evaporation rate, as expected, was observed to increase with increased drying time. Evaporation during CIR‐HAD increased with increasing distance from the centreline of the sample surface. The simulation results of water and vapour flux revealed that moisture transport around the surfaces and sides of the sample is as a result of capillary diffusion, binary diffusion, and gas pressure in both the vertical and horizontal directions. The nonuniform dominant infrared heating caused the heterogeneous distribution of product temperature. These results suggest that CIR‐HAD of food occurs in a non‐uniform manner with high vapour and water concentration gradient between the product core and the surface. CONCLUSIONS: This study provides in‐depth insight into the physics and phase changes of food during CIR‐HAD. The multiphase model has the advantage that phase change and impact of CIR‐HAD operating parameters can be swiftly quantified. Such a modelling approach is thereby significant for further development and process optimization of CIR‐HAD towards industrial upscaling. © 2020 Society of Chemical Industry